Aplikasi Android Untuk Pelaporan Perlengkapan Jalan di Kota Banjarmasin - Muhammad Haykam Imama; Aridhanyati Arifin (Jurnal Teknologi Terpadu, 2022)
As the highway organizer, the Department of Transportation of Banjarmasin City has complaints about web-based road equipment applications because it takes a long time to load web pages. This condition makes work efficiency go down. As a result, services to the community could be more optimal. This research designs and builds a system called “Sistem Informasi Perlengkapan Jalan” (Road Equipment Information System) with an android base. This research purpose is to create an efficient android-based road equipment system. The hope is that it will become an alternative solution to help the Department of Transportation of Banjarmasin City maintain road equipment. The research stages consist of three stages: data collection, literature study, and software development. Data collection uses two techniques, namely interviews and observation. The development method used is Extreme Programming (XP). The application is built using Android Studio tools, Java programming language, and MySQL database. The testing method used is black box testing. The result of the research is a system that can accurately accommodate road equipment data and accurately display the location of the intended road equipment on the map. In addition, the Android-based SIPJ application is more efficient than the web-based SIPJ based on access speed.